Estado actual de la terapia antiangiogénica en el manejo de gliomas de alto grado - Sinning O., Mariana; Fodor B., Miguel; Wiechmann De B., Eduardo; Pugin A., Ángela; Lemus A. , David (Revista Hospital Clínico Universidad de Chile, 2008)
High grade gliomas are lethal cancers. Despite recent advances in surgery, radiotherapy and chemotherapy, the overall survival is 15 months for glioblastoma. They are among the most vascular of human tumors, making them especially attractive targets for angiogenesis inhibitors. Most clinical trials of these agents as monotherapy have failed to demonstrate survival benefit in unselected high grade glioma patient populations. Several mechanisms of treatment failure have been postulated. In response, there are new intervention strategies on course: the combination of target therapy with clasic chemotherapy, multitargeted kinase inhibitors and combinations of single-targeted kinase inhibitors and the identification of correlative biomarkers. These advances provide real opportunities for the development of effective therapies for high grade gliomas.